HUBUNGAN DUKUNGAN KELUARGA DENGAN DURASI IBU MEMBERIKAN ASI EKSKLUSIF - Muhti, Isna Farihah; Agrina, Agrina; Sabrian, Febriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
This study aimed to identify the relationship of family support with the duration of exclusive breastfeeding in Sidomulyo Public Health Center Pekanbaru. This research uses descriptive correlation design with the cross sectional approach. Respondents in the study were mothers who had infants aged 6-12 months as many as 97 people, that were taken using purposive sampling technique. The measuring tool used was questionnaire with 19 statements for family support variables and 2 statements for the duration of exclusive breastfeeding that has passed validity and reliable testing. Data analysis used was univariate & bivariate analysis using the chi-square test. The results showed that most respondents gave positive family support (50.5%) and the duration of exclusive breastfeeding <6 months (66.0%). Mothers with exclusive breastfeeding duration for 6 months were mothers with positive family support (55.1%). The relationship between family support and mother duration gave exclusive breastfeeding was significant, with p-value (0,000) <Î± (0,005) OR = 8,591. It is expected that health workers can enhance their active role by providing health education on the importance of exclusive breastfeeding and family to always support the mother to do exclusive breastfeeding.Keywords: Duration, exclusive breastfeeding, family support.